О взаимодействии окисей олефинов с ароматическими соединениями - Левин В. А.; Тронов Б. В. Борис Владимирович; Лопатинский В. П. Вадим Петрович; Сироткина Е. Е. Екатерина Егоровна (1969, 1969)
Заглавие с титульного листа